Application of Fuzzy Logic in Servo Motor - Abd-Alkarim, Shereen F. (Al-Khwarizmi Engineering Journal, 2007)
In this work the design and application of a fuzzy logic controller to DC-servomotor is investigated. The proposed strategy is intended to improve the performance of the original control system by use of a fuzzy logic controller (FLC) as the motor load changes. Computer simulation demonstrates that FLC is effective in position control of a DC-servomotor comparing with conventional one.